Weed Management by Acacia Organic Mulch In Soybean For Sustainable Agriculture And Food Security - Anuar Ramut (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2026)
The application of organic mulch derived from plants containing allelopathic compounds, which can suppress weed growth in soybean fields. This study aims to evaluate the effectiveness of reduced acacia organic mulch dosages as an adaptive and efficient weed management innovation that contributes to sustainable agriculture practices and reinforces national food security.The study was conducted in Lawe Sagu Hulu Village, Lawe Bulan Sub-district, Southeast Aceh Regency, Indonesia, from August to December 2024. The experimental design employed a single-factor Randomized Complete Block Design (RCBD) with five treatment levels of acacia organic mulch dosage: 0, 4.8, 9.6, 14.4, and 19.2 tons ha?¹, each replicated four times. The acacia litter used as organic mulch was cut into 10 cm pieces and spread evenly on the soil surface according to the treatment dosage. Observed parameters included weed cover percentage, number of species, and fresh weed biomass, plant height and number of leaves, number of pods, seeds, and dry seed yield per plant. Data were analyzed quantitatively using SPSS version 16. When significant effects were detected, mean separation was conducted using DNMRT at a 5% significance level. The application of acacia organic mulch at a dosage of 4.8 tons ha?¹ reduced weed cover percentage at 20, 30, 40, and 50 days after planting and increased plant height at 30 days as well as the number of pods per soybean plant. The dosage of 9.6 tons ha?¹ of acacia organic mulch decreased weed fresh weight at 30 and 50 days after planting.